African politics meets Chinese engineers: The Chinese-built Standard Gauge Railway Project in Kenya and East Africa - Uwe Wissenbach; Yuan Wang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
This paper examines the way local Kenyan politics have affected implementation of the Standard Gauge Railway. It points to initial and immediate development opportunities for local content, jobs, and skills while arguing for a more rigorous assessment of the SGR's economic development potential. Unless Kenya overhauls its governance framework on the issues outlined in this paper, infrastructure projects risk overshooting initial budgets. This may also reduce the willingness of neighboring countries or foreign investors to engage in future initiatives in Kenya.
Keywords: 330